2017
DOI: 10.1590/0074-02760170046
|View full text |Cite
|
Sign up to set email alerts
|

Increased peripheral blood TCD4+ counts and serum SP-D levels in patients with chronic paracoccidioidomycosis, during and after antifungal therapy

Abstract: BACKGROUNDThe main clinical forms of paracoccidioidomycosis (PCM) are the acute/subacute form (AF) and the chronic form (CF), and they both display considerable clinical variability. The immune responses of PCM patients, during and after treatment, remain neglected, mainly in the case of CF patients, due to the high prevalence of pulmonary sequelae.OBJECTIVETo evaluate the distribution of whole blood T cell subsets, serum cytokines, and biomarkers of pulmonary fibrosis in PCM patients, according to the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In recent years, our group has focused on the study of pulmonary sequelae in patients with CF-PCM, and our findings have shown pro-fibrotic alterations since diagnosis along with prolonged systemic and low-grade pro-inflammatory profiles during and after a complete and successful antifungal therapy [ 6 , 7 , 8 , 9 , 10 ]. In addition, we previously established a murine model of pulmonary PCM, in which BALB/c mice presented with intense pulmonary fibrosis (PF), and we evaluated antifibrotic drugs and combined antifungal therapies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our group has focused on the study of pulmonary sequelae in patients with CF-PCM, and our findings have shown pro-fibrotic alterations since diagnosis along with prolonged systemic and low-grade pro-inflammatory profiles during and after a complete and successful antifungal therapy [ 6 , 7 , 8 , 9 , 10 ]. In addition, we previously established a murine model of pulmonary PCM, in which BALB/c mice presented with intense pulmonary fibrosis (PF), and we evaluated antifibrotic drugs and combined antifungal therapies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical aspects of PCM PS have rarely been studied [ 5 , 30 ], and although fibrogenesis in PCM is recognized as an early process [ 31 34 ], the molecular mechanisms involved in these sequela are still unknown. Our group has observed several immunological alterations in these patients even after successful antifungal treatment, including increased levels of pro-inflammatory cytokines and growth factor [ 35 ], high counts of CD14 + CD16 ++ monocyte subsets [ 34 ], high counts of peripheral blood TCD4 + [ 35 ], increased counts of peripheral blood plasmacytoid dendritic cells [ 36 ], and enhanced inflammasome activation [ 37 ]. These findings highlights the complexity of a sequelae in these patients along with systemic repercussion.…”
Section: Introductionmentioning
confidence: 99%